Recreational and tourist destination research methods - Tetiana Bozhuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The methodological basis of the concept RTDe are the main provisions of the modern structural and socio-economic geography to study the spatial and temporal aspects of relations in the system "Man - Nature" and related sciences (knowladge about a tourizm, recreational geography, natural resources, etc.) that appeal to spatial heterogeneity of the studied phenomena. In accordance with the established scientific and methodological principles, fundamental circuit and algorithm design-geographical research foundations RTDe system applied research methods in accordance with the objectives of objects and levels of study.